The removal of toxic heavy metals from aqueous solutions by algal extracellular polysaccharides - Selepe, Mamaropeng Marcus (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
This study investigated the possible use of algal extracellular polysaccharide as a biosorbent for removal of heavy metals (copper and lead) from aqueous solutions as a means of bioremediation for metal containing effluents. This biopolymer has good biosorbent properties and a potential to provide a cost effective, selective and efficient purification system. A variety of environmental conditions induce the production of extracellular polysaccharides in algae. The production of exopolysaccharides by Dunaliella cultures was induced by nitrogen deficient conditions. A high ratio of carbon to nitrogen source considerably enhanced the polysaccharide release. Purified extracellular polysaccharide samples exhibited a monosaccharide composition consisting of the following sugars: xylose, arabinose, 2-0-methyl mannose, mannose, glucose and galactose. The relative abundance (%) of these sugars were calculated relative to xylose. The major sugar constituent was 2-0-methyl mannose, which was present at approximately 160% relative to xylose. The percentage relative abundance of other sugars was as follows: 18.8; 86.8; 85.3 and 22.3% for arabinose; mannose; glucose and galactose respectively. The identity of the various constituents were confirmed by mass spectrometry. The ability of Dunaliella exopolysaccharides to accumulate metals was investigated. The following parameters were studied because they affect metal uptake: solution pH, biomass concentration, temperature, time and metal concentration. The uptake of both copper and lead were pH dependent. However, metal uptake was not significantly affected by temperature. Kinetic studies showed that Dunaliella extracellular polysaccharides exhibit good bioremediation properties. Metal uptake was rapid. In addition, the exopolysaccharide has good metal binding capacity with an uptake capacity for lead of 80 mg/g from a solution containing initial lead concentration of approximately 40 mg/l. Competition studies revealed that the presence of a second metal in solution inhibits uptake of the other metal compared to uptake in single metal solution of that particular metal. The presence of lead inhibited the uptake of copper from approximately 65% in single metal solution to 10% in binary metal solution. The presence of copper also inhibited lead uptake, though not to the same extent. Higher concentrations of lead could not completely prevent removal of copper from solution and visa versa. The same was true for lead which could not be displaced by a four-fold concentration of copper. Instead, a certain percentage of copper was always removed showing that lead did not compete with copper for these binding sites. In conclusion it appears that, copper and lead bind to different sites on Dunaliella exopolysaccharides and that they exhibit selective or preferential removal of lead.
Keywords: Heavy metals -- Absorption and adsorption; Copper; Lead; Algae -- Biotechnology; Polysaccharides -- Biotechnology